Perlindungan Hukum Bagi Penyewa Yang Telah Membayar Lunas Terkait Pengakhiran Perjanjian Sewa Akibat Keadaan Kahar - Pontoh, Sunita Caroline; Sahril, Iran; Marniati, Felicitas Sri (DAS Institute, 2025)
This research aims to analyze the legal consequences of terminating a lease agreement due to force majeure concerning payments that have been entirely made by the lessee, as well as legal protection for the lessee regarding the leased object that cannot be enjoyed due to force majeure. This study uses a normative legal research method to examine relevant laws and regulations, court decisions (Case Approach), and relevant legal concepts. The study results indicate that in a force majeure situation, the lessee generally cannot claim compensation based on the Civil Code. However, applying the concept of The Law of Restitution can provide fairer legal protection, requiring the lessor to return the value of benefits received if the leased object cannot be enjoyed. This research concludes that further regulation regarding force majeure in the Civil Code is necessary to provide legal certainty and justice for the parties in a lease agreement.